Evaluasi Daya Dukung Fondasi Tiang Menggunakan PDA dan CAPWAP pada Gardu Induk - Rabiya; Suratmin; Nur Aida (Jurnal Karajata Engineering, 2026)
Extra-high voltage substations require reliable pile foundations to ensure structural stability and safety. One method of evaluating the bearing capacity of pile foundations in the field is dynamic testing using a Pile Driving Analyzer or PDA combined with CAPWAP analysis. This study aims to evaluate the bearing capacity of pile foundations at extra-high voltage substations based on PDA test results and compare them with analytical calculations using the Meyerhof method. The testing was conducted on two installed pile foundations using the high strain dynamic testing method in accordance with the ASTM D4945 standard. Field data was obtained from measurements of force and velocity during hammering, then analyzed using CAPWAP software to determine the characteristics of tip resistance and skin friction. The analysis results showed that the ultimate bearing capacity based on the Meyerhof method was 1884.96 kN, while the CAPWAP analysis results showed a lower end bearing capacity, namely 167.3 kN for pole P-1 and 11.6 kN for pole P-2. This significant difference indicates that the dynamic test results are greatly influenced by soil conditions and soil-pile interaction in the field. This finding emphasizes the importance of using dynamic tests as a field evaluation to verify analytical calculation results in pile foundation design.